Longitudinal impact of machiavellianism on adolescent prosocial behavior and suicidal risk: the role of hope and loneliness - Kaixuan Gao; Fengling Fang (BMC Psychology)
Abstract Background Adolescence represents a pivotal stage marked by substantial physiological and psychological transformations, during which prosocial behavior and suicide risk are of paramount concern. Machiavellianism, a personality trait encompassing self-centeredness, utilitarianism, and manipulativeness, may exert an influence on these behaviors. This study was designed to explore the impact of Machiavellianism on adolescent prosocial behavior and suicide risk, with a specific emphasis on the mediating effects of hope and loneliness. Methods A sample of 618 Chinese middle school students (mean age: 13.65 years) participated in this study by completing assessments of Machiavellianism, hope, loneliness, prosocial behavior, and suicide risk at two distinct time points. Structural equation modeling techniques were utilized to investigate the mediating roles of hope and loneliness. Results The findings revealed a negative correlation between Machiavellianism and prosocial behavior, as well as hope, while a positive association was observed between Machiavellianism and loneliness and suicide risk. Furthermore, hope and loneliness emerged as mediators in the relationship between Machiavellianism and both prosocial behavior and suicide risk, with hope functioning as a protective factor and loneliness serving as a risk factor. Conclusion The study offers valuable insights into the intricate interplay among Machiavellianism, hope, loneliness, prosocial behavior, and suicide risk in adolescents. Understanding these intricate relationships can guide the development of targeted mental health interventions aimed at addressing the needs of high-risk youth.